INTERNATIONAL ASPECTS OF THE SPANISH CIVIL WAR, 1936-1939 AND THE EVOLUTION OF ANGLO-GERMAN RELATIONS ON THE EVE OF WORLD WAR II - Malay, Vera; Krupskaya, Svetlana; Timoshkova, Olga; Fomichev, Nickolay; Orechova, Marina (Revista Inclusiones, 2020)
The article, based on an analysis of British foreign policy documents and materials of the Archive of the Foreign Policy of the Russian Federation, examines Anglo-German relations in the second half of the 1930s. It reveals how official London in the context of the internationalization of the Spanish Civil War, 1936-1939 built its relations with Berlin, which has failed to achieve in bilateral and international relations and why.